Teacher training in transition to inclusive education - Kimhi, Yael; Bar Nir, Aviva (Frontiers in Education, 2025)
IntroductionThis study explores how inclusive education is addressed in teacher training programs in Israel, with a focus on the perspectives of participants who are actively engaged in the process.MethodsUsing a qualitative, inductive design, 34 semi-structured interviews were conducted with teacher candidates, pedagogical counselors, program heads, school principals, and mentor teachers across four teacher education colleges and eight partner schools.FindingsThematic analysis revealed four interrelated themes: the value of practical fieldwork experience, the need for stronger theoretical foundations in inclusion, challenges in bridging theory and practice, and the importance of professional development for teacher educators. Methodological triangulation across diverse roles enhanced the validity of the findings and allowed for a multidimensional understanding of the systemic and practical challenges in preparing teachers for inclusive classrooms.DiscussionThe findings identified a clear need for reform, redesigning the teacher education programs, and a need for guidelines regarding the curriculum of teacher-training programs for inclusive education. The study concludes with recommendations for redesigning teacher education programs, including closer integration of theory and practice, embedding Universal Design for Learning (UDL) principles, and supporting educators through structured mentorship and ongoing training.